In Vivo Distribution of Helicobacter felis in the Gastric Mucus of the Mouse: Experimental Method and Results - Schreiber, Sören (American Society for Microbiology, 1999)
We describe a method that permits the collection of very small samples (2 nl) from precisely defined positions within the gastric mucus of anesthetized mice. This method was used to study the in vivo local distribution of bacteria within the mucus of Helicobacter felis-infected mice. A total of 200 samples from 40 mice were analyzed. Each sample was microscopically analyzed, within less than 1 min, as a native preparation. To avoid changes in bacterial location within the mucus after collection and to improve the counting accuracy, bacterial motility was blocked by adjusting the pH inside the collecting pipette to 4.5. The mucus in a collected sample was subdivided into three layers, an epithelial layer (the first 25 μm of mucus from the tissue-mucus interface), a luminal layer (the last 25 μm to the mucus-lumen interface), and the remaining central mucus layer. The volume of the analyzed segments in the sample was between 4 and 9 pl. The concentration of bacteria inside the epithelial mucus layer was 3,400 per nl, but it was only 50 per nl inside the central mucus layer. The mean distance of H. felis to the epithelial surface was 16 μm. A total of 75% of all H. felis bacteria resided in the mucus zone between 5 and 20 μm from the tissue surface, with no bacteria closer than 5 μm to the epithelial surface. This method permits the study of factors determining the density of colonization and distribution of bacteria along chemical gradients with a high precision.